2021
DOI: 10.1073/pnas.2021852118
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectome fingerprinting using shallow feedforward neural networks

Abstract: Although individual subjects can be identified with high accuracy using correlation matrices computed from resting-state functional MRI (rsfMRI) data, the performance significantly degrades as the scan duration is decreased. Recurrent neural networks can achieve high accuracy with short-duration (72 s) data segments but are designed to use temporal features not present in the correlation matrices. Here we show that shallow feedforward neural networks that rely solely on the information in rsfMRI correlation ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Functional connectome fingerprinting has been an active area of research (Abbas et al, 2020; Amico & Goñi, 2018; Finn et al, 2015; Griffa et al, 2022), but these studies have primarily involved modest numbers of individuals from single high-quality datasets. Neural network applications in this area are also not new (Misra et al, 2021; Sarar et al, 2021; Wang et al, 2019), but again, these studies have not looked at repurposing the intermediate representation of these models for new data. We achieve near ceiling accuracy on multiple datasets, even when scan duration is severely limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional connectome fingerprinting has been an active area of research (Abbas et al, 2020; Amico & Goñi, 2018; Finn et al, 2015; Griffa et al, 2022), but these studies have primarily involved modest numbers of individuals from single high-quality datasets. Neural network applications in this area are also not new (Misra et al, 2021; Sarar et al, 2021; Wang et al, 2019), but again, these studies have not looked at repurposing the intermediate representation of these models for new data. We achieve near ceiling accuracy on multiple datasets, even when scan duration is severely limited.…”
Section: Discussionmentioning
confidence: 99%
“…These are derived using a given dataset’s subject identifiers and not anyone’s real-world identities. Functional connectome fingerprinting in particular has a long history as a research topic and has proven to be a powerful representation of brain function that quantifies a person’s brain activity by correlating brain region responses over time (Abbas et al, 2020; Amico & Goñi, 2018; Griffa et al, 2022; Sarar et al, 2021; Van De Ville et al, 2021; Wang et al, 2019). Functional connectome fingerprinting has achieved impressive accuracy for recognizing individuals across tasks (Finn et al, 2015) and can be used to predict cognitive performance (Rosenberg et al, 2016; 2020) and traits of individuals (Greene et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Fingerprint Property of Children's FNC Brain FC and its network analog, FNC, are believed to provide a window into brain function and intrinsic brain organization 2,37−39 . Neuroimaging studies have successfully established that adults' FC pro le shows substantial inter-subject variability, and such variability can distinguish individuals from another scan 7,12 . Unlike adults, children might show more intra-subject variability in FC due to the developments in the brain 40 .…”
Section: Discussionmentioning
confidence: 99%
“…FC heterogeneity has long been appreciated in fMRI studies, even within the same population [8][9][10] . By using a multi-condition fMRI dataset from the Human Connectome Project, studies have shown that FC pro le can distinguish adult subjects across scan sessions and even between distinct task conditions 7,11,12 , acting as a " ngerprint". A recent study has captured ve different functional clusters in the pulvinar with speci c connectivity ngerprints, which are associated with distinct components of cognition 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Because resting‐state FC is thought to characterize intrinsic functions (Biswal et al, 1995 ), it has been frequently employed in various studies. For example, previous reports have identified individuals using their FC information obtained from rfMRI (Cai et al, 2020 ; Chen & Hu, 2018 ; Demeter et al, 2020 ; Finn et al, 2015 ; Finn et al, 2017 ; Horien et al, 2019 ; Pallarés et al, 2018 ; Sarar et al, 2021 ). In this context, there have been attempts to uncover the distinguishing interindividual differences of FCs.…”
Section: Introductionmentioning
confidence: 99%